Strategic Decision-Making Agility and Organizational Resilience During Economic Uncertainty: Evidence from a Quantitative Corporate Survey - Sanco Simanullang; Leni Cahyani; Yeyen Subandi; Ratna Rintaningrum; Astri Wulandari (Ilomata International Journal of Management, 2026)
This study investigates the role of strategic decision-making agility in enhancing organizational resilience under conditions of economic uncertainty. Although prior studies have examined strategic agility and organizational performance, limited empirical research has explored the internal mechanisms linking strategic decision-making agility, dynamic capabilities, and organizational resilience in developing-country contexts. This study addresses that gap by examining the mediating role of dynamic capabilities and the moderating role of digital readiness. A quantitative approach was employed using survey data collected from 250 managers working in manufacturing, logistics, and service companies. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that strategic decision-making agility positively affects organizational resilience and significantly strengthens dynamic capabilities. Dynamic capabilities were also found to positively influence organizational resilience and partially mediate the relationship between strategic decision-making agility and organizational resilience. In addition, digital readiness significantly moderates the relationship between strategic decision-making agility and organizational resilience, indicating that organizations with stronger technological preparedness are better able to translate agile decision-making into resilience outcomes. This study contributes to strategic management literature by integrating strategic decision-making agility, dynamic capabilities, digital readiness, and organizational resilience into a single empirical framework within a developing-country context. The findings suggest that organizational resilience during periods of economic uncertainty depends not only on rapid and adaptive decision-making, but also on the organization’s capability development and technological preparedness.